Towards a co-creative recapitalization of territorial systems - Luciano De Bonis; Eugenio Leanza; Jesse Marsh; Ferdinando Trapani (European Regional Science Association (ERSA), 2014)
In European and national policies it is by now evident that the approach to spatial issues favours "economic reasons" over "territorial reasons". The recent emphasis on "cities as drivers of development", although an improvement over previous programming periods, remains fully situated within this logic. The reasons for this economic imperative are somewhat comprehensible, as the EU struggles to respond to the deep economic crisis, with its territories more vulnerable than ever to the negative consequences of globalization as a consequence of the single market and monetary union. It is however less easy to understand the fact that any consideration of "urban assets" and their management is equally overshadowed in both the rhetoric and the practice of European ? and even more, national and regional ? spatial programming, especially considering the effective contribution to an understanding of economic and financial dynamics and potentials. The thesis here is that the dichotomy between economic and territorial logics can be overcome if the framework of analysis shifts from "management of territorial impacts" to the "co-design of territorial visions", as the two become intimately intertwined in an approach of "territorial innovation". This in turn shifts the reading of territorial assets from a mere accounting of static value to a recapitalization of local contexts as a function of their innovation potential, allowing for the dynamics of development to reach self-sustainability in both territorial and economic-financial terms while evolving in concert with global flows. Prerequisite for this co-evolutionary, self-sustainable recapitalization of local settings is the consideration of the human, cultural, and social dimensions as integral components of territorial capital, together with the need for co-creative approaches to the planning, implementation, and management of digital and urban agendas, seen as inseparable more than simply interconnected.
Keywords: 330; territorial capital; territorial innovation; co-creativity